Lesson of the month: Oxycodone-induced leukoencephalopathy: a rare diagnosis - Jones, Eleanor (Clin Med (Lond), 2020)
Oxycodone-induced leukoencephalopathy is a rare diagnosis that should be considered in unconscious patients with appropriate history. We describe a case of a 57-year-old unconscious woman who required intubation and did not respond to naloxone infusion. The unconsciousness was initially thought to be due to hypoxic brain injury. However, a further review of brain imaging showed characteristic features of oxycodone-induced leukoencephalopathy. We describe the pathological and radiological features of this condition, and provide a concise review of the limited literature on this condition. Accurate diagnosis of this condition will be valuable to clinicians and patients in terms of their medium-term and long-term prognosis, and potential for rehabilitation.